1994
DOI: 10.1038/368651a0
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin interacts with amphiphilic peptides composed of all D-amino acids

Abstract: Calmodulin binds to amphiphilic, helical peptides of a variety of amino-acid sequences. These peptides are usually positively charged, although there is spectroscopic evidence that at least one neutral peptide binds. The complex between calmodulin and one of its natural target peptides, the binding site for calmodulin on smooth muscle myosin light-chain kinase (RS20), has been investigated by crystallography and NMR which have characterized the interactions between the ligand and the protein. From these data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
44
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 25 publications
6
44
0
Order By: Relevance
“…Melittin appears to suppress HIV LTR activity in a Tat-independent manner, indicating that melittin influences cellular transcription factors of the HIV LTR. As a membrane-active peptide, melittin is capable of interfering with cellular signal transduction pathways in different ways, including activation of phospholipase A2 (Clark et al, 1987 ;Sharma, 1993), and decreasing activities of calmodulin (Fisher et al, 1994) and protein kinase C (Gravitt et al, 1994). These properties may change the balance and activities of cellular stimulators of HIV transcription, such as NFκB, AP-1 and NFAT (Makropoulos et al, 1996 ;Hoover et al, 1996 ;Hill & Treisman, 1995 ;Crabtree, 1989 ;Gaynor, 1992) or induce inhibitory factors, analogous to the interferon-induced cellular inhibitor of HIV transcription (Tissot & Mechti, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Melittin appears to suppress HIV LTR activity in a Tat-independent manner, indicating that melittin influences cellular transcription factors of the HIV LTR. As a membrane-active peptide, melittin is capable of interfering with cellular signal transduction pathways in different ways, including activation of phospholipase A2 (Clark et al, 1987 ;Sharma, 1993), and decreasing activities of calmodulin (Fisher et al, 1994) and protein kinase C (Gravitt et al, 1994). These properties may change the balance and activities of cellular stimulators of HIV transcription, such as NFκB, AP-1 and NFAT (Makropoulos et al, 1996 ;Hoover et al, 1996 ;Hill & Treisman, 1995 ;Crabtree, 1989 ;Gaynor, 1992) or induce inhibitory factors, analogous to the interferon-induced cellular inhibitor of HIV transcription (Tissot & Mechti, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Calmodulin has also been shown to be able to bind a wide range of smaller ligands, including polypeptides, in which the interaction takes place between amino acid side chains [5,6]. Peptides with little sequence homology, however, are capable of binding to calmodulin, though the majority of peptides that do so have a high propensity to form an amphipathic ␣-helix [7,8] and contain a cluster of basic residues.The interaction between calmodulin and the ␣-helical peptide melittin has been the subject of a number of investigations over the years using a range of spectroscopic approaches [9 -17]. Fluorescence and circular dichroism spectroscopy have revealed that in the presence of calcium, both calmodulin and melittin undergo significant structural changes, particularly in the vicinity of tyrosine residues 99 and 138 in calmodulin and at tryptophan 19 in melittin [9].…”
mentioning
confidence: 99%
“…Calmodulin has also been shown to be able to bind a wide range of smaller ligands, including polypeptides, in which the interaction takes place between amino acid side chains [5,6]. Peptides with little sequence homology, however, are capable of binding to calmodulin, though the majority of peptides that do so have a high propensity to form an amphipathic ␣-helix [7,8] and contain a cluster of basic residues.…”
mentioning
confidence: 99%
“…Since numerous ligand-target interactions are stereospecific, one means to both examine the nature of the A␤-cellular interactions and assess the validity of several proposed mechanisms of A␤-induced cell death is to determine whether A␤ bioactivity exhibits stereospecificity. Similar issues of ligand stereospecificity have been investigated in several recent studies by comparing the binding and or activities of D-and L-enantiomers of small peptide ligands (15,16). In the current study, we have utilized a comparable paradigm, synthesizing the all-D-and all-L-amino acid stereoisomers of the truncated biologically active A␤ [25][26][27][28][29][30][31][32][33][34][35] and the full-length A␤ 1-42 peptide, and compared their physical and biological properties to determine whether the interaction of A␤ with biologically relevant cells is stereospecific.…”
mentioning
confidence: 99%
“…In two recent studies for example, the all-Dpeptide analogs were found to bind with similar affinities to their respective receptors. In the first one, two all-D-amphiphilic helical peptides were shown to interact with calmodulin in a sterically malleable fashion (16,33), and the second example reported that the laminin segment containing the IKVAV amino acid sequence, which is responsible for cell attachment and tumor-promoting activities, was retained in the all-D-peptide. Peptide analogs with either alternating D-L-substitutions or randomized IKVAV sequence were inactive, indicating that the sequence and conformational status of the domain contribute to the biological activity but that no stereospecific requirement exists (15).…”
mentioning
confidence: 99%